INTERNAL QUALITY ASSURANCE IN EDUCATIONAL INSTITUTIONS UNDER THE SECONDARY EDUCATION SERVICE AREA OFFICE BANGKOK 1 - Meeyaikachpak , Pawarisa; Dejbamrung , Sombat (Journal of MCU Nakhondhat, 2023)
The objective of this research is to study the internal quality assurance of education within schools affiliated with the Secondary Education Service Area Office Bangkok 1. and to study the development guidelines for internal quality assurance in schools affiliated with the Secondary Education Service Area Office Bangkok 1 survey research. The population consists of teachers from schools affiliated with the Secondary Education Service Area Office Bangkok 1, Group 3, totaling 627 individuals. The sample group consists of 86 individuals. using questionnaires and interviews, the statistics utilized include frequency, percentage, mean, and standard deviation. The research findings indicate that 1) The internal quality assurance within schools affiliated with the Secondary Education Service Area Office Bangkok 1 is overall at a high level. The highest average score is in the area of setting educational standards for schools, followed by monitoring and improving the school's performance to meet the educational standards, and the lowest is in the area of developing the school to meet the educational standards. 2) The research proposes the following guidelines for the development of internal quality assurance in schools affiliated with the Secondary Education Service Area Office Bangkok 1 1) project to promote understanding of the educational standards among teachers and educational committee members to participate. 2)project to provide knowledge about developing an educational management plan to create a systematic process of educational management development. 3) project to promote collaboration in implementing project activities. 4) project to enhance understanding of evaluating and verifying the quality of education within the schools. 5)project to encourage teacher and staff participation in summarizing the operational results according to the annual plan to obtain empirical data. 6) project to develop a self - assessment reporting system to the public 7) project to promote collaboration in developing an internal quality assurance system within the educational institution, following the recommendations of the Secondary Education Service Area Office or the Basic Education Commission Office, for planning and summarizing activities and results.